Experimental investigation and numerical analysis of precast reinforced concrete shear walls with shoe bolt connections. Issue 2 (January 2023) - Chong, Xun; Zhao, Meng; Huang, Jun-Qi; Jiang, Qing; Li, Hao-Ran; Feng, Yu-Long
An innovative shoe bolt connection for precast concrete (PC) structures that features resilience is proposed in this study. In this connection, a steel washer plate that could be easily replaced after an earthquake serves as the "fuse" element, and the bolt passing through the horizontal joints serves as the self-centring element. To validate the reliability of the proposed connection, quasi-static tests were conducted on two PC shear wall specimens. One specimen was designed with a conventional wall shoe bolt connection (S-1). The other specimen was designed with the proposed connection (S-2). The crack pattern, failure mode, hysteresis curve, skeleton curve, ductility and energy dissipation capacity of the specimens were studied. Furthermore, finite element (FE) analysis was conducted to reproduce the test and facilitate an in-depth understanding on the mechanism of the specimens. The test and analysis results indicated that S-1 exhibited brittle failure, while the failure of S-2 was governed by concrete crushing and fuse plate yielding and reflected a remarkable self-centring capacity; only minor shear slips of the horizontal joints occurred, even for the specimen S-1 with a smaller axial load ratio, indicating that the joints had enough shear resistance; the proposed three-dimensional FE model could predict the skeleton curve and the failure mode of the specimens with acceptable accuracy; for the specimen with proposed connection, the failure mode was significantly influenced by the thickness of the fuse plate.